Nutritional recommendations for water polo - Cox, G. R.; Mujika, I.; van den Hoogenband, C.-R. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Water polo is an aquatic team sport that requires endurance, strength, power, swimming speed, agility, tacti- cal awareness, and specific technical skills, including ball control. Unlike other team sports, few research- ers have examined the nutritional habits of water polo athletes or potential dietary strategies that improve performance in water polo match play. Water polo players are typically well muscled, taller athletes; female players display higher levels of adiposity compared with their male counterparts. Positional differences exist: Center players are heavier and have higher body fat levels compared with perimeter players. Knowledge of the physical differences that exist among water polo players offers the advantage of player identification as well as individualizing nutrition strategies to optimize desired physique goals. Individual dietary counseling is warranted to ensure dietary adequacy, and in cases of physique manipulation. Performance in games and during quality workouts is likely to improve by adopting strategies that promote high carbohydrate availability, although research specific to water polo is lacking. A planned approach incorporating strategies to facilitate muscle glycogen refueling and muscle protein synthesis should be implemented following intensified training sessions and matches, particularly when short recovery times are scheduled. Although sweat losses of water polo players are less than what is reported for land-based athletes, specific knowledge allows for appropriate planning of carbohydrate intake strategies for match play and training. Postgame strategies to manage alcohol intake should be developed with input from the senior player group to minimize the negative consequences on recovery and player welfare.